Inclusive Communication: An Experience in Creation of Campaigns on Intellectual Disability - de Andrés del Campo, Susana; González Martín, Rodrigo (Área Abierta. Revista de comunicación audiovisual y publicitaria, 2012)
This article describes the development of a teaching practice done with students of Advertising and Communication for Social Purposes. The first part of this article places the academic foundation and purposeful framework of the new European Higher Education Area in which the project is contextualized and directed. After a deliberation on the most appropriate framework to address the relationship between communication and disability, the article takes the idea of inclusive communication, reaching an aspirational definition of it. On this conceptual base, we illustrate the teaching methodology designed to promote practical learning in creating campaigns for the rights of people with intellectual disabilities. The aim of the experience is to advance creative innovation of the images and representations of people with intellectual disabilities, creating mock campaigns, from experiential learning and an inclusive process that takes into account the participation and evaluation of communication experts on disability, as well as the persons the ads referred. As a result of innovation we relate unprecedented issues, claims and representations, and discuss how the learning process influences the composition of a certain ideology that the participant students had designed about the role that advertising can play in relation to the social problem of intellectual disability. The article concludes by assessing the processes of social research based on creativity.